1991
DOI: 10.4315/0362-028x-54.8.627
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Aflatoxin in Peanut Butter From 1982 to 1989

Abstract: Randomly chosen, commercially available, market basket samples of on-the-shelf brands of peanut butter were routinely tested for the presence of aflatoxin from 1982 to 1989. Standard analytical procedures were employed which included high performance liquid chromatography and thin layer chromatography. During the eight years studied, 74% of the samples were positive for the presence of aflatoxin. Of those samples testing positive which excluded no detect samples or “zero values”, 8.6% were found to be contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Crops from anywhere in the U.S. may be affected, depending on the growth, harvesting, and storage conditions involved; however, aflatoxin contamination is particularly high in warm, dry regions of the Southeast. A study of 2510 peanut butter samples from 1982 to 1989 showed that about 10% exceeded the FDA action level for aflatoxin (31).…”
Section: Mycotoxin Exposure Worldwide and Implications Of Regulationsmentioning
confidence: 99%
“…Crops from anywhere in the U.S. may be affected, depending on the growth, harvesting, and storage conditions involved; however, aflatoxin contamination is particularly high in warm, dry regions of the Southeast. A study of 2510 peanut butter samples from 1982 to 1989 showed that about 10% exceeded the FDA action level for aflatoxin (31).…”
Section: Mycotoxin Exposure Worldwide and Implications Of Regulationsmentioning
confidence: 99%